Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1073/pnas.75.4.2040
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary adaptation of membranes to temperature.

Abstract: The "fluidity" of brain synaptosomal membrane preparations of arctic and hot-springs fish species, two temperate water fish species acclimated to different seasonal temperatures, and two mammals was estimated using the fluorescence polarization technique. At all measurement temperatures, the fluidity decreased in the order: arctic sculpin, 50-acclimated goldfish, 250-acclimated goldfish, desert pupfish, and rat. This correlated with increasing adaptation or body (i.e., cellular) temperatures of 0°, 50, 250, 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
100
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(111 citation statements)
references
References 11 publications
6
100
0
1
Order By: Relevance
“…Phospholipids from specific membranes of an Arctic marine fish proved more unsaturated than those of subtropical freshwater fish, and these differences were reflected in the microviscosity ofthese structures (8). The present article compares the liver phospholipid compositions of a number of marine and freshwater fish, and a feasible mechanism is proposed to explain the adaptational phenomena at a membrane structural level.…”
mentioning
confidence: 98%
“…Phospholipids from specific membranes of an Arctic marine fish proved more unsaturated than those of subtropical freshwater fish, and these differences were reflected in the microviscosity ofthese structures (8). The present article compares the liver phospholipid compositions of a number of marine and freshwater fish, and a feasible mechanism is proposed to explain the adaptational phenomena at a membrane structural level.…”
mentioning
confidence: 98%
“…The most compelling evidence for this mechanism stems from data where the ratio sats/unsats follows a linear progression when plotted against the membrane fluorescence polarisation of diphenyl hexatrine (DPH) (Cossins and Prosser, 1978), for animal species adapted to different mean habitation temperatures, as reviewed (Hazel, 1995). The argument that general rule across a homologous headgroup series, increases in saturated hydrocarbon chain length increase the value of T m and increasing cis unsaturation decreases the value of T m .…”
Section: Introductionmentioning
confidence: 99%
“…In development of HVA, Sinensky (Sinensky, 1974) observed using Electron Spin Resonance (ESR) that the order parameter of E. coli membranes remained constant, determined as a function of spin probe rotational correlation time, despite their phospholipid compositions changing in response to different growth temperatures. Subsequently, evidence for HVA as a conserved evolutionary mechanism emerged (Behan-Martin et al, 1993;Cossins and Prosser, 1978) and HVA has since been reported under many other changing environmental conditions, such as in response to hydrostatic pressure (Behan et al, 1992;Macdonald, 1986, 1984), osmotic pressure (Laroche et al, 2001) , low magnetic field strength (Santoro et al, 1997) and chemicals such as PCB-153 (Gonzalez et al, 2013), mitelfosine (Rybczynska et al, 2001) and crude oil (Mazzella et al, 2005). To date evidence for HVA has been found in species across the three domains of life and it is arguably the most widely used theory to explain phospholipid compositional changes, usually through the concept of maintaining membrane fluidity or membrane viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the PUFA content might be expected to rise when acclimating animals to lower temperatures. 3 In studies on fish, 24,34,35 this effect was mainly seen in the content of EPA and DHA. The fatty acid content of phospholipids from seven different Atlantic cod tissues was reported in an earlier study.…”
mentioning
confidence: 99%
“…On the other hand, it is generally assumed that a higher average chain length would point in the direction of warm acclimation due to the ability of longer acyl chains to pack more tightly and reduce the viscosity of the membranes. 3,35 Unlike the BLM, the BBM side of the cell can be expected to be more atypical in comparison with non-epithelial cells. It has been documented earlier that BBM shows the inverse compensation behavior compared with BLM when either rainbow trout (Oncorhynchus mykiss) or common carp (Cyprinus carpio) were acclimated to the cold, that is, the BBM was shown to become more viscous 4,6 when adapting to cold.…”
mentioning
confidence: 99%